Efektivitas Edukasi Ibu dalam Penatalaksanaan Ruam Popok pada Bayi Baru Lahir - Ayu Landari; Nevi Susianty (STIKes Ibnu Sina Ajibarang, 2025)
Diaper rash is among the most common dermatological problems experienced by neonates, particularly during the first few weeks of life. It is characterized by erythema, irritation, and discomfort in the diaper area, and may progress to secondary bacterial or fungal infections if not properly managed. Several contributing factors include prolonged exposure to urine and feces, mechanical friction from diapers, increased skin humidity, and inadequate perineal hygiene. This condition may negatively affect the infant’s comfort, disrupt sleep quality, and interfere with feeding patterns due to irritability and fussiness. Therefore, early identification and appropriate management are essential to prevent further complications and to support neonatal well-being. This study aimed to evaluate the effectiveness of maternal education in diaper rash management as part of holistic midwifery care. A case was observed in a 17-day-old infant, Baby Ny. S, at TPMB Bdn. Silvi Ayu, S.Keb Pekanbaru, who presented with mild to moderate diaper rash. The intervention consisted of structured maternal education focusing on proper diaper hygiene, the importance of frequent diaper changes, and the correct application of zinc oxide-based protective ointment. The program was implemented and monitored over five consecutive days. The results demonstrated significant clinical improvement, with reduced redness, irritation, and overall skin recovery. In addition, the mother showed increased knowledge and awareness regarding newborn skin care, highlighting the role of education in preventive neonatal health practices. This finding emphasizes that effective diaper rash management involves not only pharmacological or topical treatment but also active maternal participation through education and routine preventive measures. In conclusion, maternal education serves as a key strategy in reducing the incidence and severity of diaper rash. Midwives, by providing comprehensive, evidence-based education and care, play a vital role in preventing neonatal skin complications and promoting optimal health and development in newborns.